To etch or not to etch, Part I: On the fatigue strength and dentin bonding performance of universal adhesives - Stape Thiago Henrique Scarabello; Viita-aho Tapio; Sezinando Ana; Wik Patrik; Mutluay Murat; Tezvergil-Mutluay Arzu (ELSEVIER SCI LTD, 2025)
Objective. To characterize whether the bonding performance and fatigue strength of resin-dentin interfaces created by a universal adhesive would be affected by different H3PO4-application times to more accurately assess long-term durability.Methods. Mid-coronal flat dentin surfaces with standardized smear-layers were produced on sound third molars, etched with 32% H3PO4 for 0, 3 and 15 s, bonded with a mild universal adhesive (3M-ESPE) and restored with a nanofilled composite. Bonded specimens (0.9 x 0.9mm) were stored in deionized water for 24 h and sectioned into beams for microtensile testing (n = 10). Resin-dentin beams were tested under tension until failure (0.5 mm/min) after 24 h or 6 month storage in artificial saliva at 37 degrees C. Bar-shaped resin-dentin beams (0.9 x 0.9 x 12 mm) were tested under 4-point-flexure initially at quasi-static loads (n = 22) and then under cyclic loads (n > 50). The stress-life fatigue behavior was evaluated using the twin-bonded interface approach by the staircase method at 4 Hz. Fractured interfaces and the tension side of unfractured beams were evaluated under SEM, along with the micromorphology of the etched dentin surfaces and hybrid layers. Data were analyzed by ANOVA and Tukey test and Wilcoxon Rank Sum Test (alpha = 0.05).Results. Quasi-static loads were limited to discriminate the bonding performance of resin-dentin interfaces. Application modes significantly affected etching patterns, fatigue strength, endurance limits and hybrid layer morphology (p < 0.001).Significance. Reductions in fatigue strength of self-etched bonded interfaces raise concerns about the true ability of universal adhesives to properly bond to dentin. (C) 2021 The Authors. Published by Elsevier Inc.